2013
DOI: 10.1016/j.pmrj.2013.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Test‐Retest Reliability of the ABILHAND Questionnaire in Persons With Chronic Stroke

Abstract: BackgroundReliable and valid outcome measures are needed to be able to evaluate recovery, effects of rehabilitation interventions, and changes over time. The ABILHAND Questionnaire is a measure of a patient's self‐reported ability to perform complex daily activities involving use of the hand. This instrument is commonly used in stroke rehabilitation settings, but data about the measurement variability are missing.ObjectiveTo assess the test‐retest reliability of the ABILHAND Questionnaire in persons with chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 37 publications
6
47
0
2
Order By: Relevance
“…The higher the logit value, the better the self-perceived ability to use the upper extremities in daily hand activities. In this study, the Swedish version of the ABILHAND was used [23], which has been shown to have acceptable test-retest reliability for persons with mild to moderate impairments of the upper extremities after stroke [8]. Due to cultural differences the item ‘Peeling potatoes with a knife’ was changed to ‘Peeling potatoes’ (as a potato-peeler is commonly used in Sweden) and in the item ‘Tearing open a pack of chips’ the following words were added ‘ or a candy-bag’ (because older persons in Sweden more rarely eat chips) [8].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher the logit value, the better the self-perceived ability to use the upper extremities in daily hand activities. In this study, the Swedish version of the ABILHAND was used [23], which has been shown to have acceptable test-retest reliability for persons with mild to moderate impairments of the upper extremities after stroke [8]. Due to cultural differences the item ‘Peeling potatoes with a knife’ was changed to ‘Peeling potatoes’ (as a potato-peeler is commonly used in Sweden) and in the item ‘Tearing open a pack of chips’ the following words were added ‘ or a candy-bag’ (because older persons in Sweden more rarely eat chips) [8].…”
Section: Methodsmentioning
confidence: 99%
“…The advantage of using questionnaires is that they often provide a better understanding of an individual’s self-reported everyday difficulties and thereby enable clinicians to design more individually targeted rehabilitation interventions [6]. One questionnaire that is recommended for persons with disability of the upper extremity after stroke is the ABILHAND Questionnaire [4, 7, 8]. It assesses self-perceived ability to perform daily bimanual activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Test-retest reliability was excellent when tested in subjects 6 to 48 months post-stroke. 28 In this study, raw scores were converted into logits using online analysis (http://www.rehab-scales.org).…”
Section: Abilhand Questionnairementioning
confidence: 99%
“…A vantagem das medidas lineares é que elas podem oferecer resultados cientificamente mais robustos e clinicamente mais significativos do que medidas ordinais, ao permitir inferências corretas a partir de comparações diretas inter ou intraindivíduos 11 . O ABILHAND, específico para indivíduos pós-AVE, foi utilizado em estudos prévios 12,13 e apresentou adequada validade de construto 7 e confiabilidade testereteste 14 . Além disso, pode ser recomendado para uso clínico, por pontuar nove em 10 na escala de utilidade clínica de Tyson e Connell, que avalia o tempo de aplicação, custo, necessidade de equipamento, treinamento especial e portabilidade 15 .…”
Section: Introductionunclassified